Stink and the great Guinea Pig Express - McDonald, Megan; Reynolds, Peter, 1961- (London : Walker Books, 2008)
Stink Moody, friends Webster and Sophie, and Mrs. Birdwistle visit tourist attractions in Virginia as they try to give away 101 guinea pigs rescued from a laboratory, although Stink is very reluctant to relinquish his favorite, Astro.
3.4
K-3.
K-3
Keywords: Animal rescue -- Juvenile fiction; Automobile travel -- Juvenile fiction; Guinea pigs -- Juvenile fiction; Animal rescue -- Fiction; Automobile travel -- Fiction; Guinea pigs -- Fiction; Humorous stories; Animal welfare -- Fiction; Automobile travel -- Fiction; Guinea pigs -- Fiction; Humorous fiction; Virginia -- Juvenile fiction; Virginia -- Fiction; Virginia -- Fiction; Humorous fiction